Transcranial Direct Current Stimulation in neurogenetic syndromes: new treatment perspectives for Down syndrome? - Faralli, Alessio; Fucà, Elisa; Lazzaro, Giulia; Menghini, Deny; Vicari, Stefano; Costanzo, Floriana (Frontiers in Cellular Neuroscience, 2024)
This perspective review aims to explore the potential neurobiological mechanisms involved in the application of transcranial Direct Current Stimulation (tDCS) for Down syndrome (DS), the leading cause of genetically-based intellectual disability. The neural mechanisms underlying tDCS interventions in genetic disorders, typically characterized by cognitive deficits, are grounded in the concept of brain plasticity. We initially present the neurobiological and functional effects elicited by tDCS applications in enhancing neuroplasticity and in regulating the excitatory/inhibitory balance, both associated with cognitive improvement in the general population. The review begins with evidence on tDCS applications in five neurogenetic disorders, including Rett, Prader-Willi, Phelan-McDermid, and Neurofibromatosis 1 syndromes, as well as DS. Available evidence supports tDCS as a potential intervention tool and underscores the importance of advancing neurobiological research into the mechanisms of tDCS action in these conditions. We then discuss the potential of tDCS as a promising non-invasive strategy to mitigate deficits in plasticity and promote fine-tuning of the excitatory/inhibitory balance in DS, exploring implications for cognitive treatment perspectives in this population.